2020
DOI: 10.1021/jacs.0c00650
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Induced Stromal Depletion to Enhance the Penetration of Gemcitabine-Loaded Magnetic Nanoparticles for Pancreatic Cancer Targeted Therapy

Abstract: Pancreatic ductal adenocarcinoma, as one of the most aggressive cancers, is characterized by rich desmoplastic stroma that forms a physical barrier for anticancer drugs. To address this issue, we herein report a two-step sequential delivery strategy for targeted therapy of pancreatic cancer with gemcitabine (GEM). In this sequential strategy, metformin (MET) was first administrated to disrupt the dense stroma, based on the fact that MET downregulated the expression of fibrogenic cytokine TGF-β to suppress the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 60 publications
(84 reference statements)
0
113
0
Order By: Relevance
“…Recent studies have suggested that CAFs were derived from MSCs, which may be either populated in the pancreas or recruited by neoplastic cells [7,30]. Whereas pancreatic stellate cells from mice or from human patients were used in previous studies [31,32], they were unstable and quite variable, as their characteristics were not accurately assessed. We focused on AD-MSCs as the source of CAFs because they are available, easy to handle, and are multipotent, allowing their differentiation into CAFs [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that CAFs were derived from MSCs, which may be either populated in the pancreas or recruited by neoplastic cells [7,30]. Whereas pancreatic stellate cells from mice or from human patients were used in previous studies [31,32], they were unstable and quite variable, as their characteristics were not accurately assessed. We focused on AD-MSCs as the source of CAFs because they are available, easy to handle, and are multipotent, allowing their differentiation into CAFs [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al indicated that metformin suppressed paracrine-mediated activation of PSCs in the coculture setting of PCCs–PSCs ( 200 ). Han et al revealed that metformin inhibited the PSC-mediated desmoplastic reactions, thus reducing tumor size and improving the perfusion of GEM-loaded magnetic nanoparticles in a murine orthotopic PDAC model ( 157 ). More recently, metformin was shown to suppress angiogenesis and increase GEM chemosensitivity via deactivating PSCs in KPC mice ( 201 ).…”
Section: Current Progress In Targeting Strategiesmentioning
confidence: 99%
“…Findings suggested that targeted delivery and effective accumulation of the nanomedicine both in vitro and in vivo. Furthermore, the configuration change of pHLIP is controlled by the acidic environment of the tumor, which is beneficial to deliver GEM into the tumor sites [ 127 ].…”
Section: Application and Clinical Trials Of Nanocarrier-based Thermentioning
confidence: 99%